HER2-targeted therapies for HER2-positive early-stage breast cancer: present and future - Luying Xu; Luying Xu; Yuxin Xie; Yuxin Xie; Qiheng Gou; Rui Cai; Rui Cai; Rong Bao; Rong Bao; Yucheng Huang; Yucheng Huang; Ruisi Tang; et al. (Frontiers Media S.A., 2024)
Breast cancer (BC) has the second highest incidence among cancers and is the leading cause of death among women worldwide. The human epidermal growth factor receptor 2 (HER2) is overexpressed in approximately 20%-30% of BC patients. The development of HER2-targeted drugs, including monoclonal antibodies (mAbs), tyrosine kinase inhibitors (TKIs) and antibody-drug conjugates (ADCs), has improved the operation rate and pathological remission rate and reduced the risk of postoperative recurrence for HER2-positive early-stage BC (HER2+ EBC) patients. This review systematically summarizes the mechanisms, resistance, therapeutic modalities and safety of HER2-targeted drugs and helps us further understand these drugs and their use in clinical practice for patients with HER2+ EBC.